Strengthening governance and leadership of the national laboratory system in Liberia: achievements and challenges - Torbandu H. Kohar; Ellen Munemo; Jonathan Kpaka; Nisha Marles; Ochiawunma Akwiwu-Ibe; Anicet G. Dahourou; Frantz Jean Louis (Frontiers in Public Health)
BackgroundLiberia’s health system, severely impacted by prolonged conflict and the 2014–2015 Ebola outbreak, suffered from critical gaps in laboratory governance, workforce capacity, and diagnostic infrastructure. To address these challenges, the Ministry of Health (MoH), in collaboration with international partners, launched a national reform initiative aimed at strengthening the laboratory system. This study assesses the implementation and outcomes of the revised National Laboratory Policy and Strategic Plan introduced in 2019.MethodsA situational analysis was conducted to identify systemic weaknesses. The MoH formed a Technical Working Group to develop and implement the revised policy and plan. Qualitative and quantitative data were gathered through stakeholder interviews, document reviews, and laboratory quality audits.InterventionsThe reform focused on five key areas: enhancing governance structures, expanding workforce development, implementing quality management systems (QMS), integrating private laboratories into the national network, and formalizing national laboratory policies and strategic guidelines.ResultsSubstantial improvements were observed across intervention areas. Governance was enhanced through strengthened roles of the National Diagnostic Division and National Public Health Institute of Liberia. A Bachelor of Medical Laboratory Science program was launched, with its first cohort enrolled in 2023. Eighteen laboratories joined a structured QMS program, and three attained a one-star rating. Four private laboratories were integrated into national disease surveillance. Comprehensive policy documents and infrastructure, equipment, and quality assurance guidelines were developed and disseminated.ConclusionLiberia has made measurable progress in laboratory governance, workforce development, and quality assurance. Sustained investment in policy implementation, training, and infrastructure is critical to preserving these gains and improving national health security.